1996
DOI: 10.1111/j.1365-2427.1996.tb01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel, episodic and seasonal changes in pH and concentrations of inorganic carbon in a productive lake

Abstract: S U M M A R Y1. Two pH electrodes and a thermistor were used to record conditions in the surface of Esthwaite Water every 15 min over a 12-month period. Combined with approximately weekly measurements of alkalinity they allowed inorganic carbon speciation to be calculated. 2. Large changes in pH from 7.1 to nearly 10.3, and hence in concentrations of inorganic carbon species, were measured over a year. Carbon speciation and pH varied on a diel, episodic and seasonal basis. Diel variation of up to pH 1.8 was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
206
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(221 citation statements)
references
References 43 publications
14
206
1
Order By: Relevance
“…However, in productive systems the rate of carbon-fixation in a unit volume of water can greatly exceed rates of carbon supply from the atmosphere, or other sources, leading to depletion of CO 2 virtually to zero (Maberly 1996) limiting productivity (Ibelings and Maberly 1998;Jansson et al 2012). Furthermore, the rate of CO 2 diffusion in water is about 10 4 -times lower in water than in air (Raven 1970) leading to substantial transport limitation through the boundary layer surrounding objects in water (Black et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, in productive systems the rate of carbon-fixation in a unit volume of water can greatly exceed rates of carbon supply from the atmosphere, or other sources, leading to depletion of CO 2 virtually to zero (Maberly 1996) limiting productivity (Ibelings and Maberly 1998;Jansson et al 2012). Furthermore, the rate of CO 2 diffusion in water is about 10 4 -times lower in water than in air (Raven 1970) leading to substantial transport limitation through the boundary layer surrounding objects in water (Black et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…These have much lower buffering capacity than the oceans, so significant daily variations in pH occur as a result of normal temporal phasing of net photosynthesis and net respiration. For example, Maberly (1996) showed that diel variations in a lake can be as much as 2-3 pH units. In contrast, the pH change in the ocean is expected to be B0.3 pH units over the next 100 years.…”
Section: Ocean Acidification and Microbesmentioning
confidence: 99%
“…Table 2. These data are representative of the lake at all times, except during short periods in summer when high algal productivity causes higher pH (Maberly, 1996). Samples (50 l) were collected by wading into the small stream that is the lake outflow.…”
mentioning
confidence: 99%